An investigation into the specialized skills and knowledge required for Forensic Social Work practice in South Africa - Mangezi, Martin Simbarashe (Department of Social Development, 2018)
In era of prevalent crime and social problems in South Africa, the National Department of Social Development; the South African Council of Social Service Professions and tertiary institutions are rethinking strategies to respond to these issues. A central strategy behind this is the development of forensic social work practice as a specialist service in order to assist the criminal justice system to deal effectively with offenders and protect victims. The aim of this study was to investigate the specialized skills and knowledge required for forensic social work practice in South Africa. Literature acknowledges that forensic social work is still a developing field of practice in South Africa hence forensic social work practitioners require effective training to competently practice forensic social work. The research design adopted by the study is a combination research design comprising of both quantitative and qualitative approaches. The research empirical data was obtained through the use of questionnaires from a survey conducted in Gauteng Province, South Africa at a forensic social work training workshop in 2013. The study indicated that forensic social work practitioners are familiar with some of the specialized skills such as language used in court, writing skills, communication and engagement skills and professionalism. The study also indicated that forensic social work practitioners are also familiar with some of the knowledge such as the definition of forensic social work, legal aspects, criminal justice system, courtroom procedures and knowledge required to act as an expert witness in court for forensic social work practice. However, despite this, forensic social work practitioners had inadequate training in the specialized skills and knowledge required to competently practice forensic social work in South Africa. In addition, the study showed that there are many challenges faced by forensic social work practitioners. Challenges include lack of resources, undermining of forensic social work practitioners by other professionals, adoption of international standards, registration, role specification and lack of collaboration with other professionals. The author recommended that forensic social work practitioners in South Africa require further training in legislation, policies and the specialized skills and knowledge relevant for forensic social work practice and finding solutions to overcome the challenges faced. Further research should be conducted in other provinces in South Africa for forensic social work.